Răspuns :
A = (1 + 2 + 3 +...+ 2000) × 2001^2000
A = 2000 × 2001 : 2 × 2001^2000
A = 1000 × 2001^2001
A = 10^3 × (2001^667)^3 este cub perfect
A = 2000 × 2001 : 2 × 2001^2000
A = 1000 × 2001^2001
A = 10^3 × (2001^667)^3 este cub perfect
A=(1+2+3+....+2000)×2001^2000
S=1+2+........+2000
S=2000+1999+1998+.....+1
adunând sumele
2S=2001+2001+......+2001 de 2000ori
S=2001×2000:2
S=2001×1000
înlocuind in A
A=2001×1000×2001^2000
A=1000×2001^2001
A=10^3×(2001^667)^3
A=(10×2001^667)^3
S=1+2+........+2000
S=2000+1999+1998+.....+1
adunând sumele
2S=2001+2001+......+2001 de 2000ori
S=2001×2000:2
S=2001×1000
înlocuind in A
A=2001×1000×2001^2000
A=1000×2001^2001
A=10^3×(2001^667)^3
A=(10×2001^667)^3